Estimation of Slip Distribution of the 2007 Bengkulu Earthquake from GPS Observations Using the LeastSquares Inversion Method - Irwan Meilano; Sri Widiyantoro; Moehammad Awaluddin (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
Continuous Global Positioning System (GPS) observations showed significant crustal displacements as a result of the Bengkulu earthquake occurring on September 12, 2007. A maximum horizontal displacement of 2.11 m was observed at PRKB station, while the vertical component at BSAT station was lifted up with a maximum of 0.73 m, and the vertical component at LAIS station had subsided